PANDANREJO TOURISM VILLAGE DIGITAL BRANDING IDENTITY ANALYSIS - Dendy Sundayana; Linandar Tanuwijaya; Mohamad Ridwan; Darmawan Sundayana; Odang Rusmana (International Journal of Sustainable Competitiveness on Tourism, 2024)
Tourism is one of the factors affected by the COVID-19 pandemic, but after the COVID-19 pandemic, tourism began to rise. There was the phenomenon of "Revenge Tourism," or revenge tourism, which increased interest in travelling after the COVID-19 pandemic. There is also an alternative trend in the form of tourist villages, which are increasingly growing. Pandanrejo Tourism Village is one of the tourist villages in Indonesia and has various attractions and tourism products that are attractive to tourists. The aim of this research is to determine how the digital branding of a tourist village can be right on target according to the target market they determine and what the condition of the village's digital branding identity is. This must be supported by the use of strong branding, both digital and conventional. However, for branding the Pandanrejo Tourism Village, there are still several things that can be maximised so that digital communication through digital branding includes concepts and visual designs carried out in tourism products so that it can maximise the target market and positioning of the Pandanrejo Tourism Village. This research approach uses a qualitative research approach with several key sources to be used as primary data for analysis and involves many stakeholders, such as tourist village managers, community leaders, village officials, and visitors who came to this village. The findings in this research are the condition of the digital branding of the Pandanrejo tourist village and the implications for the information conveyed to visitors.